EFFECT OF SEED SOURCE AND SEED SIZE ON THE EARLY GROWTH OF ANACARDIUM OCCIDENTALE SEEDLINGS - Yisau, J. A.; Emilimor, P. N; Odeyale, O. C.; Majolagbe, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Seed size and seed origin forms a very important element in the quality of seedlings produced in the nursery. This study investigated the effects of seed size and seed source on early growth of Anacardium occidentale seedlings. Seeds collected from mother tree at three sources (Somorin, Funaab and Camp locations) were sorted into Large, Medium and Small sizes. Collected and sorted seeds, raised in 54 poly pots was laid out in 3 x 3 factorial in Completely Randomized Design (CRD). Data was collected fortnightly for 12 weeks and it was subjected to Analysis of Variance (ANOVA) in SAS. Large sized seed had significantly (p
Keywords: Seed source; seed size; Anacardium occidentale; seedling growth